2012
DOI: 10.2105/ajph.2012.300687
|View full text |Cite
|
Sign up to set email alerts
|

A New Framework for Childhood Health Promotion: The Role of Policies and Programs in Building Capacity and Foundations of Early Childhood Health

Abstract: Although the connection between early life experiences and later health is becoming increasingly clear, what is needed, now, is a new organizing framework for childhood health promotion, grounded in the latest science. We review the evidence base to identify the steps in the overall pathway to ensuring better health for all children. A key factor in optimizing health in early childhood is building capacities of parents and communities. Although often overlooked, capacities are integral to building the foundati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 91 publications
1
82
0
4
Order By: Relevance
“…Countries with high levels of inequality, as in the case of Chile, must incorporate public policies for social protection to address poverty and the generated vulnerability (18)(19)(20) . The results of the present study demonstrated the precarious living conditions of the mothers and children, as well as the gap between the expected and observed results from the access to the benefits and/or services guaranteed by law (1) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Countries with high levels of inequality, as in the case of Chile, must incorporate public policies for social protection to address poverty and the generated vulnerability (18)(19)(20) . The results of the present study demonstrated the precarious living conditions of the mothers and children, as well as the gap between the expected and observed results from the access to the benefits and/or services guaranteed by law (1) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the children and their mothers were admitted early and displayed good compliance with the health controls and although the professionals applied screening protocols for risks and psychosocial problems, there was no timely and focused management to ensure the access to preventive health services and the protection of comprehensive development in all of the children and women at psychosocial risk, as has been recommended in the reviewed literature (18)(19)(20)(21) . This fact is relevant because the "Chile Grows with You" program offers a range of services beginning with pregnancy and because the purpose of these services is to encourage early emotional ties between the children and their primary caregivers, thereby building a parental framework in which a secure attachment is essential for each stage of child development (3) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Este ponto de vista é particularmente valioso para a compreensão do potencial das políticas e programas voltados para a primeira infância, sob o intuito de produzir benefícios à vida adulta (1) . É importante, então, o enfoque na promoção da saúde e prevenção das doenças em crianças, a fim de proporcionar crescimento e desenvolvimento saudáveis.…”
Section: Introductionunclassified